Penerapan Pembelajaran Maharah Kalam di Universiti Sultan Zainal Abidin Malaysia - Syifani, Yusliha; Fauji, Imam; Murshidah, Nik (Universitas Islam Ahmad Dahlan Sinjai, 2025)
Arabic language learning, especially speaking skills (maharah kalam), is an important aspect in mastering a foreign language. This study aims to analyze the implementation of maharah kalam learning at Universiti Sultan Zainal Abidin (UniSZa), including preparation, implementation, and supporting and inhibiting factors. The research method used is descriptive qualitative with interview, observation, and documentation techniques. The results of the study indicate that maharah kalam learning at UniSZa focuses on communication practices through the muhadatsah method, the use of digital media such as YouTube and audio, and evaluation based on communication skills. Supporting factors include the availability of technological facilities, a supportive academic environment, and a communicative approach in teaching. However, there are several obstacles such as the lack of language practice outside the classroom and the limited number of competent teaching staff. In addition, supporting programs such as mukhayyam lughawi and the use of technology in learning contribute to improving students' speaking skills. By implementing effective and innovative methods, maharah kalam learning at UniSZa can improve students' Arabic language competence so that they are more confident in cross-cultural communication.